2022
DOI: 10.1039/d2tb00997h
|View full text |Cite
|
Sign up to set email alerts
|

Orientation-controlled crystallization of γ-glycine films with enhanced piezoelectricity

Abstract: Glycine, the simplest amino acid, is considered a promising functional biomaterial owing to its excellent biocompatibil-ity and strong out-of-plane piezoelectricity. Practical applications require glycine films to be manufactured with their...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Bottom: Crystal growth kinetics of glycine-PVA films when the liquid film had a convex (green) or concave (red) edge. Reprinted with permission from ref . Copyright 2022 Royal Society of Chemistry.…”
Section: Amino Acids and Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bottom: Crystal growth kinetics of glycine-PVA films when the liquid film had a convex (green) or concave (red) edge. Reprinted with permission from ref . Copyright 2022 Royal Society of Chemistry.…”
Section: Amino Acids and Peptidesmentioning
confidence: 99%
“…Because the misalignment was due to the tilted interface where the nucleation occurs, Sui et al presented a modified strategy to move the nucleation site of γ-glycine crystals to the flat interface area. 71 In their approach, a hydrophilic wall was added around the liquid precursor film. This changed liquid film edge from a convex surface to a concave surface.…”
Section: Amino Acids and Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works to obtain noncentrosymmetric crystals of amino acid derivatives have been reported by the groups of Leiserowitz and Lahav. To complete the reductionist approach for minimal building blocks of proteins and peptides, recent studies have shown that extremely simple amino acids could self-assemble into well-ordered noncentrosymmetric architectures exhibiting significant piezoelectric characteristics. ,, For example, γ-glycine crystals showed a piezoelectric longitudinal strain coefficient d 33 of 9.93 pm V –1 , comparable to inorganic AlN or Al 3 AsO 7 , which could be applied to fabricate a piezoelectric nanogenerator for an energy harvesting of 0.45 V . Furthermore, high-quality piezoelectric crystalline thin films were synthesized by aligning γ-glycine crystals between polymer layers, serving as an implantable electromechanical device. , In another example, tyrosine crystals with tightly packed face-to-face dimers possessed high thermal stability and robust mechanical properties . The predicted piezoelectric response of tyrosine crystals (d 25 = 9.73 pm V –1 ) was shown to be comparable to those of traditional inorganic materials (e.g., ZnO, CdS) and biological materials (e.g., bone, viruses, fibrillar rat tail collagen).…”
Section: Introductionmentioning
confidence: 99%
“…4,5,38−40 V −1 , comparable to inorganic AlN or Al 3 AsO 7 , which could be applied to fabricate a piezoelectric nanogenerator for an energy harvesting of 0.45 V. 14 Furthermore, high-quality piezoelectric crystalline thin films were synthesized by aligning γ-glycine crystals between polymer layers, serving as an implantable electromechanical device. 41,42 In another example, tyrosine crystals with tightly packed face-to-face dimers possessed high thermal stability and robust mechanical properties. 43 The predicted piezoelectric response of tyrosine crystals (d 25 = 9.73 pm V −1 ) was shown to be comparable to those of traditional inorganic materials (e.g., ZnO, CdS) and biological materials (e.g., bone, viruses, fibrillar rat tail collagen).…”
Section: ■ Introductionmentioning
confidence: 99%